Aegilops Species for the Improvement of the Leaf and Stripe Rust Resistance in Cultivated Triticale (×Triticosecale Wittmack) - Waldemar Ulaszewski; Michał Tomasz Kwiatek (Agronomy, 2020)
Hexaploid triticale (×Triticosecale Wittmack, 2n = 6x = 42 chromosomes, AABBRR) is a cultivated hybrid, which combines wheat (Triticum aestivum L.) and rye (Secale cereale L.) properties. It has a better ability to be grown on poor soils, compared to wheat. Mainly, triticale is produced for forage feed and bioethanol. Considering the limited diversity of this human-made crop, there is a need to widen its genetic variability, especially to introduce new genes, responsible for agronomic traits, such as resistance to biotic stresses. Leaf rust caused by Puccinia triticina Eriks. and stripe rust caused by Puccinia striiformis Westend are the most destructive foliar diseases of triticale and related cereals. Developing resistant triticale varieties is an important strategy for the control of these diseases. A number of leaf and stripe rust resistance genes have been already introduced into bread wheat from related species using chromosome manipulations. Exploitation of related species conferring desirable loci is the most effective non-GMO way of improving the rust resistance of triticale. The procedure encompasses chromosome doubling of obtained hybrids followed by a number of backcrosses to eliminate unnecessary alien chromatin and to reduce the linkage drag. In this review, we show the recent status of pre-breeding studies, which are focused on transfer of leaf and stripe rust resistance genes from Aegilops species into cultivated triticale using distant crossing and chromosome engineering.